2016
DOI: 10.1002/adhm.201600030
|View full text |Cite
|
Sign up to set email alerts
|

Stable Encapsulation of Air in Mesoporous Silica Nanoparticles: Fluorocarbon‐Free Nanoscale Ultrasound Contrast Agents

Abstract: While gas-filled micrometer-sized ultrasound contrast agents vastly improve signal-to-noise ratios, microbubbles have short circulation lifetimes and poor extravasation from the blood. Previously reported fluorocarbon-based nanoscale contrast agents are more stable but their contrast is generally lower owing to their size and dispersity. The contrast agents reported here are composed of silica nanoparticles of ≈100 nm diameter that are filled with ≈3 nm columnar mesopores. Functionalization of the silica surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
124
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(133 citation statements)
references
References 68 publications
(88 reference statements)
2
124
0
Order By: Relevance
“…It was observed that responsivities of the particles stored for 3 d or 14 d were almost same with the fresh particles (see the Supporting Information, Figure S6) suggesting that the nanobubbles are stable for at least two weeks, which is in accordance with our previous findings with Pluronic F127 stabilized hydrophobic MCM-41 MSNs. 29 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was observed that responsivities of the particles stored for 3 d or 14 d were almost same with the fresh particles (see the Supporting Information, Figure S6) suggesting that the nanobubbles are stable for at least two weeks, which is in accordance with our previous findings with Pluronic F127 stabilized hydrophobic MCM-41 MSNs. 29 …”
Section: Resultsmentioning
confidence: 99%
“…More recently, we showed that acoustic cavitation initiated by Pluronic polymer stabilized hydrophobic MSN, when exposed to HIFU, can be observed by using a conventional imaging transducer. 29 In these studies it was assumed that the air encapsulated inside the mesopores of silica nanoparticles initiates acoustic cavitation. Later, it was shown that the air stabilized inside the cavities of nanocups 30, 33 or even at the surface of solid hydrophobic particles 31 can also initiate acoustic cavitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahmad Nor et al prepared similar particles, with varying degrees of hydrophobicity, and demonstrated that the particles which were both rough and hydrophobic released their drug loadings slowest [224]. Yildrim et al reported that mesoporous silica nanoparticles are effective ultrasound contrast agents, by releasing or nucleating microbubbles in response to focused ultrasound [225]. Finally, Chen et al synthesized mesoporous silica nanoparticles with grafted fluorocarbons and photoresponsive spiropyran [226].…”
Section: Drug Deliverymentioning
confidence: 99%
“…Due to these limitations, perfluorocarbon-based nanodroplets have been developed, which are capable of entering tumors [164]. However, these nanodroplets have poorer contrast than the more traditional microbubbles, which is a major deterrent for use in tumor imaging [182]. Luke et al recently reported “super-resolution ultrasound imaging” of a new generation of nano-sized contrast agents, laser-activated nanodroplets (LANDs), which seem to hold future promise for deep tissue molecular imaging [183].…”
Section: Application Of Nanotechnology For Brain Cancer Imagingmentioning
confidence: 99%